تطبيقات الوقف على ميراث المرأة في مجتمع الرقيبة الجزائري: دراسة تحليلية تقويمية - Bashir, al-Khawlah Ghauri; Awang, Abdul Bari (2019)
Abstract This article discusses the waqf applications on the inheritance of women in Reguiba District of Algeria and aims to reveal the status of women in the society of Reguiba. In Reguiba, the application of endowment of inheritance is only given to males; females are excluded unjustly. There is a need of correcting this corrupt custom according to the rulings of Islamic Shariah. It will also reveal the motives of the Algerian Reguiba society for applying this injustice that is carried out by the male authority and the policy of preference which has infiltrated the mindsets of the people of Arab and Islamic societies alike. For these reasons, it is necessary to know the points of injustice, which will pave the way for speeding up the process of applying the correct Islamic laws. In this article, the researchers used the analytical and deductive approaches to produce the expected results through the review of the application of endowment of inheritance for males excluding females in the Algerian Reguiba society that is occurring in the name of so called ‘public interest’